Uncovering children reception towards children television programme in Malaysia / Shazleen Mohamed - Mohamed, Shazleen (2018)
This study is endeavoring to uncover the children reception towards children television programme in Malaysia. The study concentrated on five research objectives: (i) to identify how children express their preferences towards the television programmes (ii) to unravel how the children respond towards the television programmes they watched (iii) to reveal how children interpret the social reality and fantasies of the scenes in the television programmes they watched (iv) to determine how children identify themselves with the characters in the television programmes they watched and (v) to uncover how children being influenced in term of cognitive, affective and behavior by the television programmes they watch. This study does not attempt to observe if television has effects on children. 30 children aged between four to six years old were interviewed and observed in the study. Interviews were conducted in both English and Malay depending on the language in which the children were best able to express themselves: some were bi-lingual and some spoke only Malay. During the course of observations, the researchers watched and recorded everything the children said and did while they were viewing. Firstly, irrespective of their ages (four, five or six years old), the children managed to identify and determine what program that they like to watch. The children express their preferences based on these characteristics (i) for fun (ii) for relaxation and comfort (iii) to avoid boredom and (iv) to bond with parents and siblings. The elements that raised these pleasures include comical acts; programs suitable for their age and produced in a simple style that are comprehensible, straightforward and precise; repetition of dialogues, images and music; attractive characters and host. Secondly, the children respond towards the programs they watched through these elements (i) recapping dialogues (ii) playing with character's figure (toy) (iii) mood changes and (iv) Digital Video Disc (DVD) and YouTube. Thirdly, children interpret the social reality and fantasies of the scenes in the television programs they watched by (i) use imagination to express thoughts and (ii) evaluate and think before uttering their thoughts. Fourth, in relation to how children identify themselves with the characters in the television programs they watch; (i) able to identify race and citizenship (ii) able to distinguished cultural diversity. They could only visually distinguish different races or ethnicities based on body parts, skin, color and attire characteristics. Fifth, cognitively this study indicates that children experience optimistically specific basic literacy skills. Affectively the children are able to demonstrate their feelings with adequate or appropriate emotional reactions and slightly able to identify with the character's customs, manners as well as cultural heritage. Behaviorally, children unconsciously understand the sex-roles stereotyping. Data from the final analysis revealed that television did not play a major role in presenting Malaysian culture and identity to children; their cultural understanding was more influenced by everyday experience and observation.